ChemInform Abstract: Construction of Pyrrolophenanthridinone Scaffolds Mediated by Samarium(II) Diiodide and Access to Natural Product Synthesis. Issue 47 (November 2015) - Suzuki, Kenji; Iwasaki, Hiroki; Domasu, Reika; Hitotsuyanagi, Naho; Wakizaka, Yuka; Tominaga, Mao; Kojima, Naoto; Ozeki, Minoru; Yamashita, Masayuki
Abstract: A facile methodology for the construction of pyrrolophenanthridinone derivatives via a SmI2 ‐mediated reductive cyclization is developed and applied to the concise synthesis of the natural product anhydrolycorinone (IV).